The aging of ER-mitochondria communication: A journey from undifferentiated to aged cells - Morgado-Cáceres, Pablo; Liabeuf, Gianella; Calle, Ximena; Briones, Lautaro; Riquelme, Jaime A.; Bravo-Sagua, Roberto; Parra, Valentina (Frontiers in Cell and Developmental Biology, 2022)
The complex physiology of eukaryotic cells requires that a variety of subcellular organelles perform unique tasks, even though they form highly dynamic communication networks. In the case of the endoplasmic reticulum (ER) and mitochondria, their functional coupling relies on the physical interaction between their membranes, mediated by domains known as mitochondria-ER contacts (MERCs). MERCs act as shuttles for calcium and lipid transfer between organelles, and for the nucleation of other subcellular processes. Of note, mounting evidence shows that they are heterogeneous structures, which display divergent behaviors depending on the cell type. Furthermore, MERCs are plastic structures that remodel according to intra- and extracellular cues, thereby adjusting the function of both organelles to the cellular needs. In consonance with this notion, the malfunction of MERCs reportedly contributes to the development of several age-related disorders. Here, we integrate current literature to describe how MERCs change, starting from undifferentiated cells, and their transit through specialization, malignant transformation (i.e., dedifferentiation), and aging/senescence. Along this journey, we will review the function of MERCs and their relevance for pivotal cell types, such as stem and cancer cells, cardiac, skeletal, and smooth myocytes, neurons, leukocytes, and hepatocytes, which intervene in the progression of chronic diseases related to age.